Patterns of Hydroxyurea Prescription and Use in Routine Clinical Management of Polycythemia Vera: A Multicenter Chart Review Study - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Objective: This study aimed to evaluate real-life data on patterns of hydroxyurea prescription/use in polycythemia vera (PV). Materials and Methods: This retrospective chart review study included PV patients who had received hydroxyurea therapy for at least 2 months after PV diagnosis. Data were collected from 10 representative academic medical centers. Results: Of 657 patients, 50.9% were in the high-risk group (age 60 years and/or history of thromboembolic event). The median duration of hydroxyurea therapy was 43.40 months for all patients; 70.2% of the patients had ongoing hydroxyurea therapy at last followup. Hydroxyurea was discontinued in 22.4% of the patients; the most common reason was death (38.5%). The predicted time until hydroxyurea discontinuation was 187.8 months (standard error: +/- 21.7) for all patients. This duration was shorter in females (140.3 +/- 37.7 vs. 187.8 +/- 29.7) (p=0.08). This trend was also observed in surviving patients aged >= 50 years at hydroxyurea initiation (122.2 +/- 12.4 vs. 187.8 +/- 30.7, p=0.03). Among the patients who were still on hydroxyurea therapy, 40.3% had a hematocrit concentration of >= 45% at their last followup visit, and the rate of patients with at least one elevated blood cell count was 67.8%. Conclusion: Hydroxyurea prescription patterns and treatment aims are frequently not in accordance with the guideline recommendations. Its discontinuation rate is higher in females.
Keywords: Polycythemia vera; Hydroxyurea; Treatment outcome; ESSENTIAL THROMBOCYTHEMIA; PROGNOSTIC VALUE; CRITERIA; HYDROXYCARBAMIDE; INTOLERANCE; RESISTANCE; SURVIVAL; EVENTS; RISK; ELN